Edukacje duchowe. Perspektywa religioznawcza - Iwanicki, Juliusz (Polskie Towarzystwo Religioznawcze, 2014)
The article considers the different types of spiritual education. Three types are identified: classical education, Christian and alternative education. Classical education is linked to the tradition of Paideia, and the teachings of Plato. The Christian Education is associated primarily with the teachings of Augustine, but also the Polish philosopher Hessen. Alternative education is characterized by its multiplicity and represented by Rudolf Steiner’s spiritual system and the Polish school of holistic education. On the basis of comparative religion, we can divide education into denominational education and non-denominational education. The purpose of spiritual education would be finding some salvation in God, while the other forms – provide the unity of nature and freedom of the human spirit.
Keywords: duchowość; edukacja duchowa; chrześcijańska edukacja duchowa; edukacje alternatywne; klasyczna edukacja duchowa